Analysis of Foreign Accounting Techniques in Eradicating Corruption in The Public Sector - Gilbert Rely (Journal of Economics and Business (JECOMBI), 2024)
Corruption is one of the crucial problems that hinders development and public trust in government institutions. In this context, forensic accounting offers a systematic and analytical approach to identifying, preventing and addressing corrupt practices. This study aims to analyze forensic accounting techniques as a tool in efforts to eradicate corruption in the public sector. This study uses a qualitative approach with a descriptive method. The results of the study show Forensic accounting has an important role in eradicating corruption in the public sector through three stages: preventive, detective, and repressive. In the preventive stage, forensic accounting prevents corruption by implementing strict internal controls and transparent accounting practices, such as thorough audits and training for civil servants. In the detective stage, data analysis and investigation techniques are used to uncover suspicious practices and early evidence of corruption. Once corruption is detected, the repressive stage focuses on law enforcement and recovery of misappropriated assets, with forensic reports supporting legal proceedings and providing recommendations for system improvements. Collaboration between forensic accountants and law enforcement agencies further enhances the effectiveness of these efforts, so that the full application of forensic accounting can help reduce corruption and improve the integrity of the public sector.